Developing TIE “Trigonometry It’s Eazy” Games using Ispring Suite 11 for Trigonometry Learning Media - Nosi Maria Chrisa; Aldila Wanda Nugraha (International Journal of Sustainable Applied Sciences, 2024)
This development research motivates increasingly rapid technological advances, but educators must correctly use these for medical advances. This can be seen from the need for more innovation in creating exciting learning. Monotonous learning activities confuse students and affect learning outcomes, especially in trigonometry material. This research aims to develop a valid, practical, and effective TIE smartphone game media, "Trigonometry It is Eazy," based on Ispring Suite 11. This research uses the Research and Development (R&D) development method, also used in the ADDIE development process. The subjects of this research were teachers and students of grade X at Santo Thomas Aquino Catholic High School, Tulungagung, with a total of 95 students. Data collection techniques include validity questionnaires from media and material experts, teacher and student response questionnaires, and student learning outcomes tests. The validity test results from media experts obtained a score of 91.42% in the very valid category, and material experts obtained 79% in the quite valid category. The results of the practicality test by teachers were 80.86%, and students were 89.86% in the convenient category. The media effectiveness results obtained an assessment of 90.54% in the very effective category.This development research motivates increasingly rapid technological advances, but educators must correctly use these for medical advances. This can be seen from the need for more innovation in creating exciting learning. Monotonous learning activities confuse students and affect learning outcomes, especially in trigonometry material. This research aims to develop a valid, practical, and effective TIE smartphone game media, "Trigonometry It is Eazy," based on Ispring Suite 11. This research uses the Research and Development (R&D) development method, also used in the ADDIE development process. The subjects of this research were teachers and students of grade X at Santo Thomas Aquino Catholic High School, Tulungagung, with a total of 95 students. Data collection techniques include validity questionnaires from media and material experts, teacher and student response questionnaires, and student learning outcomes tests. The validity test results from media experts obtained a score of 91.42% in the very valid category, and material experts obtained 79% in the quite valid category. The results of the practicality test by teachers were 80.86%, and students were 89.86% in the convenient category. The media effectiveness results obtained an assessment of 90.54% in the very effective category.This development research motivates increasingly rapid technological advances, but educators must correctly use these for medical advances. This can be seen from the need for more innovation in creating exciting learning. Monotonous learning activities confuse students and affect learning outcomes, especially in trigonometry material. This research aims to develop a valid, practical, and effective TIE smartphone game media, "Trigonometry It is Eazy," based on Ispring Suite 11. This research uses the Research and Development (R&D) development method, also used in the ADDIE development process. The subjects of this research were teachers and students of grade X at Santo Thomas Aquino Catholic High School, Tulungagung, with a total of 95 students. Data collection techniques include validity questionnaires from media and material experts, teacher and student response questionnaires, and student learning outcomes tests. The validity test results from media experts obtained a score of 91.42% in the very valid category, and material experts obtained 79% in the quite valid category. The results of the practicality test by teachers were 80.86%, and students were 89.86% in the convenient category. The media effectiveness results obtained an assessment of 90.54% in the very effective category.